Higher education student finance between China and Australia: towards an international political economy analysis. Issue 6 (2nd November 2019) - Croucher, Gwilym; Zhong, Zhou; Moore, Kenneth; Chew, Jonathan; Coates, Hamish
ABSTRACT: This paper analyses the international financing of higher education, an important yet understudied facet of contemporary policy and practice. The paper takes the globally significant China–Australia relationship as a case study. This paper argues that analysing the international political economy of the China–Australia case better illuminates the dynamics of financials flow through situating them in their socio-political context. Through such analysis, the paper makes empirical contributions of relevance to policy and practice. It also contributes more broadly to reframing the design of work in this field by asserting the methodological need for analysing international finance and the conceptual need to take such matters into account.